2014
DOI: 10.1108/cw-10-2013-0036
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of steady-state and transient thermal properties of cermet, polymer and LTCC thick-film resistors

Abstract: Purpose -The purpose of this paper is to present the results of thermal analysis of cermet resistors made on alumina or LTCC substrate and polymer thick-film resistors embedded in FR-4 substrate. Design/methodology/approach -The study was performed using a thermal imaging method. The research was carried out with an additional consideration of such factors as sheet resistance (which depended on the type of resistive paste), the size and topology of element and the kind of contact material (Cu, Ag or Ni/Au). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…All the measurements, advanced characterizations and analyses presented above for various passive components embedded in Printed Circuit Boards as well as other our investigations not discussed in this paper (characterization of multiterminal thin-film resistors embedded in PCBs [18], determination and comparison of transient and steady-state thermal properties of thin-film, polymer and cermet thick-film as well as LTCC resistors [19], characterization of pulse durability of thin-film and polymer thick-film embedded PCB resistors [20], determination of chosen electrical and long-term stability properties of embedded capacitors and RC filters, especially with the aid of impedance spectroscopy [21,22], electrical and long-term stability characterization of planar PCB inductors [23]) confirmed that such passives with small and medium values of resistance, capacitance or inductance exhibit basic electrical properties and long-term thermal stability level acceptable for many consumer applications. …”
Section: Discussionmentioning
confidence: 99%
“…All the measurements, advanced characterizations and analyses presented above for various passive components embedded in Printed Circuit Boards as well as other our investigations not discussed in this paper (characterization of multiterminal thin-film resistors embedded in PCBs [18], determination and comparison of transient and steady-state thermal properties of thin-film, polymer and cermet thick-film as well as LTCC resistors [19], characterization of pulse durability of thin-film and polymer thick-film embedded PCB resistors [20], determination of chosen electrical and long-term stability properties of embedded capacitors and RC filters, especially with the aid of impedance spectroscopy [21,22], electrical and long-term stability characterization of planar PCB inductors [23]) confirmed that such passives with small and medium values of resistance, capacitance or inductance exhibit basic electrical properties and long-term thermal stability level acceptable for many consumer applications. …”
Section: Discussionmentioning
confidence: 99%
“…The binder polymer chain length increases with molecular weight . Slurries with lower molecular weight binders tend to have a lower viscosity and a higher solid loading, which produces green sheets with higher bulk density.…”
Section: Tape Casting Processmentioning
confidence: 99%
“…The binder polymer chain length increases with molecular weight. 78 Slurries with lower molecular weight binders tend to have a lower viscosity and a higher solid loading, which produces green sheets with higher bulk density. However, lower molecular weight binders also have lower mechanical strengths, and breakage can occur in LTCC processes if green strength is not sufficient.…”
Section: Bindermentioning
confidence: 99%